Análise da dinâmica temporal da cobertura vegetal na microrregião de Umarizal (2000 a 2022), semiárido do Rio Grande do Norte, Brasil - Islânia dos Santos Nunes; Alfredo Marcelo Grigio; Marco Antônio Diodato (Terr@ Plural)
The Caatinga, an exclusively Brazilian biome that covers several states in the Northeast of the country, has been undergoing many environmental changes, mainly about its vegetation cover and land use and occupation, consequently, the study of vegetation dynamics and knowledge of its different types of use has been widely discussed. The general objective of this work is to analyze the temporal and spatial dynamics of vegetation cover in the Umarizal micro-region, as well as knowledge of the main types of use and occupation. The methodological procedures used were satellite images from the Landsat series, specifically Landsat 5, Landsat 8, and Landsat 9, for both the dry and rainy periods of the years 2000, 2007, 2014, 2017, and 2022. For vegetation analysis, the following index was used: SAVI. QGIS Software, version 3.28.3, was used to create vegetation cover maps. To study the types of land use and occupation, data were obtained from the MapBiomas 7.1 website. After the analyses, it can be observed that SAVI values were higher in the rainy season, the year 2017 stood out for its low photosynthetic activity in both periods, due to the low levels of precipitation presented in the year in all municipalities in the micro-region. Regarding use and occupation, it was highlighted that in the micro-region the main types of use concern forest formation (savanna formation), composed of tree-shrub plant formation of deciduous forest followed by agriculture, mainly formed by temporary crops